x 3 + 2 x 2 − 3 x − 1 = 0
If a , b & c are the roots of this equation, find the value of cyc ∑ a 3 1 .
Note:
cyc ∑ denotes cyclic summation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Do you see how these expressions for \frac{1}{a}, \frac{1}{b}, \frac{1}[c} are still motivated from Newton's identities?
Exactly what I used :)
Did it the same way
i did it by puting the values of a,b,c in the given equation then adding ths all and getting the value of the expression to find !
Let us consider the transformation, x = y 1 .
y 3 1 + y 2 2 − y 3 − 1 = 0
⇒ y 3 + 3 y 2 − 2 y − 1 = 0
Let the roots of this equation be d , e , & f .
S = cyc ∑ a 3 1 = d 3 + e 3 + f 3
Defining S 1 = d + e + f , S 2 = d 2 + e 2 + f 2 and S 3 = d 3 + e 3 + f 3 ,
By Newton's Sums,
1 . S 1 + 3 = 0 ⇒ S 1 = − 3
1 . S 2 + 3 . S 1 + 2 ( − 2 ) = 0 ⇒ S 2 = 1 3
1 . S 3 + 3 . S 2 + ( − 2 ) . S 1 + 3 ( − 1 ) = 0 ⇒ S 3 = − 4 2
Hence,
S = cyc ∑ a 3 1 = d 3 + e 3 + f 3 = S 3 = − 4 2
Note:
The algebraic identity a 3 + b 3 + c 3 − 3 a b c = ( a + b + c ) ( ( a + b + c ) 2 − 3 ( a b + a c + b c ) ) come in handy for problems like this.
I agree with you challenge master.😀😀
what is newon sum ?
Given equation is :
x 3 + 2 x 2 − 3 x − 1 = 0 ⟹ 1 + x 2 − x 2 3 = x 3 1
Also, x 2 1 = x + 2 − x 3
Hence ,
x 3 1 = − 3 x − 5 + x 1 1
So, the required sum is equivalent to the following :
− 3 ( a + b + c ) − 3 ( 5 ) + 1 1 ( a 1 + b 1 + c 1 )
The above expression is easy to evaluate and gives answer as − 4 2
1 / a + 1 / b + 1 / c = − ( − 3 ) / ( − 1 ) = − 3 . 1 / a b + 1 / b c + 1 / c a = + 2 / ( − 1 ) = − 2 . 1 / a b c = − 1 / ( − 1 ) = 1 . ∴ ( 1 / a + 1 / b + 1 / c ) 2 = ( 1 / a 2 + 1 / b 2 + 1 / c 2 ) + 2 ( 1 / a b + 1 / b c + 1 / c a ) , ⟹ ( 1 / a 2 + 1 / b 2 + 1 / c 2 ) = 9 − 2 ( − 2 ) = 1 3 . 1 / a 3 + 1 / b 3 + 1 / c 3 = 3 / a b c + { 1 / a + 1 / b + 1 / c } { ( 1 / a 2 + 1 / b 2 + 1 / c 2 ) − ( 1 / a b + 1 / b c + 1 / c a ) } , = 3 + { − 3 } { 1 3 − ( − 2 ) } = − 4 2 .
Problem Loading...
Note Loading...
Set Loading...
Using Vieta's formulas, we have:
⎩ ⎪ ⎨ ⎪ ⎧ a + b + c = − 2 a b + b c + c a = − 3 a b c = 1
⇒ ⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ a 1 + b 1 + c 1 = a b c a b + b c + c a = − 3 a b 1 + b c 1 + c a 1 = a b c a + b + c = − 2 a b c 1 = 1
c y c ∑ a 3 1 = a 3 1 + b 3 1 + c 3 1 = ( a 1 + b 1 + c 1 ) ( a 2 1 + b 2 1 + c 2 1 ) − ( a b 1 + b c 1 + c a 1 ) ( a 1 + b 1 + c 1 ) + 3 ( a b c 1 ) = ( a 1 + b 1 + c 1 ) ( [ a 1 + b 1 + c 1 ] 2 − 2 [ a b 1 + b c 1 + c a 1 ] ) − ( a b 1 + b c 1 + c a 1 ) ( a 1 + b 1 + c 1 ) + 3 ( a b c 1 ) = ( a 1 + b 1 + c 1 ) 3 − 3 ( a b 1 + b c 1 + c a 1 ) ( a 1 + b 1 + c 1 ) + 3 ( a b c 1 ) = ( − 3 ) 3 − 3 ( − 2 ) ( − 3 ) + 3 ( 1 ) = − 2 7 − 1 8 + 3 = − 4 2